2019
DOI: 10.1109/access.2019.2891224
|View full text |Cite
|
Sign up to set email alerts
|

ESTHER: Joint Camera Self-Calibration and Automatic Radial Distortion Correction From Tracking of Walking Humans

Abstract: Camera calibration and radial distortion correction are the crucial prerequisites for many applications in image big data and computer vision. Many existing works rely on the Manhattan world assumption to estimate the camera parameters automatically; however, they may perform poorly when there was lack of man-made structure in the scene. As walking humans are the common objects in video surveillance, they have also been used for camera self-calibration, but the main challenges include the noise reduction for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Then, the problem is to estimate a homography given some reference elements (e.g., known objects or manual measurements) extracted from the scene or using the information of detected vanishing points in the image [4], [5], [20], [51], [58], [60], [69], [77], [109], [113]. Another common approach is to calibrate fixed cameras by observing the motion of dynamic objects such as pedestrians [53], [59], [91], [95]. Recently, approaches based on deep learning attempt at estimating directly camera pose and intrinsic parameters on a single image [41], [57].…”
Section: A Scene Geometry Understandingmentioning
confidence: 99%
“…Then, the problem is to estimate a homography given some reference elements (e.g., known objects or manual measurements) extracted from the scene or using the information of detected vanishing points in the image [4], [5], [20], [51], [58], [60], [69], [77], [109], [113]. Another common approach is to calibrate fixed cameras by observing the motion of dynamic objects such as pedestrians [53], [59], [91], [95]. Recently, approaches based on deep learning attempt at estimating directly camera pose and intrinsic parameters on a single image [41], [57].…”
Section: A Scene Geometry Understandingmentioning
confidence: 99%
“…The formula for specifying the maximum optimization velocity max ( ) v of the particles in this study is shown as (9).…”
Section: ) Proposed Pso With Apammentioning
confidence: 99%
“…Because camera calibration is an important part of image processing, scholars have conducted a lot of research in this field. Camera self-calibration [9], camera plane calibration [10] and Tsai's two-step calibration [11] are relatively mature. In recent years, several other camera calibration methods have emerged [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of MOT is to solve the following objective from an input video sequence When the camera parameters are unavailable, we first process a short period of the video sequence by preliminary 2D tracking and foreground segmentation [10]. Each human object is modeled as a pole perpendicular to the ground plane, whose endpoints are located based on the orientation of the foreground blob, from which we can compute the horizon line and vanishing points in the scene for camera self-calibration [28], [29]. An example of the estimated 3D ground plane from camera self-calibration is shown in Fig.…”
Section: A Formulation Of Data Associationmentioning
confidence: 99%
“…Because of the application of camera self-calibration [28], [29], the provided camera matrices in the MOTChallenge 3D benchmark are not adopted in our 3D MOT computation, but are only considered for evaluation. Therefore, our algorithm actually only leverages 2D information for 3D MOT.…”
Section: B Comparison With the 2d State-of-the-artmentioning
confidence: 99%